Topical analgesia treats pain and decreases propofol use during lumbar punctures in a randomized pediatric leukemia trial. Issue 1 (27th September 2014) - Whitlow, Puja G.; Saboda, Kathylynn; Roe, Denise J.; Bazzell, Susan; Wilson, Cera
<x xml:space="preserve">Abstract</x> Background Lumbar punctures are frequently performed in pediatric leukemia for central nervous system leukemic prophylaxis. The contribution of local anesthetic with deep sedation is unknown. The objective was to evaluate EMLA (eutectic mixture of local anesthetics) cream as a pain reliever in conjunction with propofol in the setting of routine lumbar punctures. Procedure We included patients with acute lymphoblastic leukemia aged 3–21 years requiring at least two routine lumbar punctures. Patients were randomly assigned to receive EMLA or placebo cream and the alternate treatment with the second procedure. Patients, personnel and outcome assessors were blinded to allocation. The primary outcome included three indirect measures of pain: total median propofol doses, patient movement and heart rate changes at the time of skin puncture in both treatment groups. Results Twenty‐six patients were enrolled and 25 were analyzed. With EMLA cream, 4 mg/kg (median) of propofol was required (95% CI 3.5–4.4). With placebo, 4.9 mg/kg of propofol was needed (95% CI 4.3–5.6; P = 0.008). When EMLA cream was applied, 8% of patients moved, whereas 84% moved with placebo cream (P < 0.0001). There was a lower average heart rate by seven beats in the EMLA treatment compared to placebo (95% CI −2.3–4.3; 4.1–12.4; P = 0.009). There were no adverse events in either treatment group. Conclusions This study demonstrated that the combination of EMLA cream with propofol is beneficial. Topical analgesics are at the discretion of the oncologist, allowing us to advocate for patients by providing safe and efficacious pain management for lumbar punctures. Pediatr Blood Cancer 2015;62:85–90. © 2014 Wiley Periodicals, Inc.